Effects of stitching yarn types on flexural fatigue properties of 3D stitched carbon fiber composites. (November 2022) - Song, Wen; Liu, Tao; Song, Chenyang; Wang, Shujuan; Jing, Yunjuan; Ma, Jun; Li, Guosheng; Zhou, Rui; Dou, Hao; Fan, Wei
Abstract: This work investigated the static bending and flexural fatigue properties of 3D stitched composites with different stitching yarns. The carbon and PBO fibers were adopted to reveal the effects of stitching yarn types on the fatigue characteristics and failure propagation of 3D stitched composites at low-stress levels by a high-speed camera. The results show that different stitching yarn types affected the static flexural strength of 3D stitched composites but did not affect their modulus. In addition, different stitching yarn types changed the fatigue failure mechanism of 3D stitched composites. The fatigue life of 3D stitched composites can be effectively improved by using PBO fibers since the PBO fiber can effectively delay shear crack growth and prolong the period of the catastrophic failure stage. This work proposed a new scheme for improving the mechanical properties of stitched composites. Highlights: Fatigue properties of composites with different stitching yarn types were studied. Failure propagation and morphologies of 3D stitched composite were captured. Fibers with stronger toughness are more suitable as stitching yarn. Interfacial behavior of stitching yarn does not affect the flexural properties.